Dynamic trunk stabilization: A conceptual back injury prevention program for volleyball athletes - Smith, C. E.; Caudill, P.; Brosky, J.; Caborn, D. N. M.; Nyland, J. A. (Journal of Orthopaedic & Sports Physical Therapy, 2008)
The sport of volleyball creates considerable dynamic trunk stability demands. Back injury occurs all too frequently in volleyball, particularly among female athletes. The purpose of this clinical commentary is to review functional anatomy, muscle coactivation strategies, assessment of trunk muscle performance, and the characteristics of effective exercises for the trunk or core. From this information, a conceptual progressive 3-phase volleyball-specific training program is presented to improve dynamic trunk stability and to potentially reduce the incidence of back injury among volleyball athletes. Phase 1 addresses low-velocity motor control, kinesthetic awareness, and endurance, with the clinician providing cues to teach achievement of biomechanically neutral spine alignment. Phase 2 focuses on progressively higher velocity dynamic multiplanar endurance, coordination, and strength-power challenges integrating upper and lower extremity movements, while maintaining neutral spine alignment. Phase 3 integrates volleyball-specific skill simulations by breaking down composite movement patterns into their component parts, with differing dynamic trunk stability requirements, while maintaining neutral spine alignment. Prospective research is needed to validate the efficacy of this program.